PELATIHAN PEMBUATAN LULUR WAJAH DARI DAUN SIRSAK (Annona Muricata L) UNTUK MENDAPATKAN KULIT SEHAT DI DESA TANJUNG ATAP - Hariani, Poedji Loekitowati; Fatma, Fatma; Said, Muhammad; Ahadito, Bijak Riyandi; Rohendi, Dedi (Jurnal Pepadu, 2025)
Facial scrubs are a part of skin care that is often done by mothers and young women. In line with back to nature awareness, body scrubs use ingredients from natural sources. This community service activity aims to provide counseling and training on the importance of skin care and making facial scrubs from soursop leaves. Soursop leaves contain bioactive ingredients which are antioxidant and antibacterial. The activity was carried out in Tanjung Atap village, Tanjung Batu sub-district, Ogan Ilir district and was attended by 26 participants. The soursop plant is easy to find in the village growing in the yard. Activity participants play an active role in activities both in counseling and training. Evaluations are carried out before and after the activity to determine the level of participants' understanding of the counseling and training provided. Apart from that, an organoleptic test was carried out to determine the level of acceptance of the body scrub product. The results of the activity showed that there was an increase in public understanding of the importance of maintaining healthy skin and making body scrubs from soursop leaves. The increase in participants' understanding was 93.03% from not understanding or not understanding. The organoleptic test results showed that 85.36% of participants said they really liked it and 14.64% said they liked the facial scrub product made from soursop leaves. With this service activity, people are increasingly aware of the importance of skin care using natural resources. Scrubs made from natural ingredients are safe, cheap and avoid the side effects of chemicals.